Analisis Strategi Promosi Bisnis Katering Pada PT. Parewa Aero Catering - Mardiana Mardiana; Eduard Hotman Purba; Joel Alfredo (UNIVERSITAS RAHARJA, 2023)
PT. PAREWA AERO CATERING is a company engaged in catering services. The purpose of this research is to develop marketing that was previously only marketed in certain places, and to formulate an effective business strategy as a suggestion for companies to improve their market competitiveness. The method used is a quantitative method, the data collection techniques used are questionnaires and interviews, then the collected data is analyzed. The conclusion drawn from the final results of the research is that the marketing strategy is the right strategy applied by the company to enter the market and compete in the market.